Regeneration method of waste lithium battery positive electrode material

By dismantling, stripping, and gradient-temperature activation of spent lithium iron phosphate batteries, combined with the use of fluorinated copolymer LiF-PAMPS, the problem of efficient regeneration of spent lithium iron phosphate batteries has been solved, the crystallinity and electrochemical performance of the materials have been improved, and green and low-carbon resource reuse has been achieved.

CN120955252APending Publication Date: 2025-11-14SHANGHAI YONGFENG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511106840.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing technologies for dismantling and sorting electrodes of waste lithium iron phosphate batteries are inefficient, pose environmental hazards, and have high energy consumption and low economic benefits in the recycling process, lacking green and low-carbon regeneration methods.

Method used

A fluorinated copolymer, LiF-PAMPS, was prepared using lithium 2-acrylamide-2-methylpropanesulfonate and dodecafluoroheptyl methacrylate through disassembly, stripping, regeneration, and activation steps. The resulting material was a regenerated cathode material obtained by activating it with gradient heating to form a conductive network, repairing the LiFePO4 crystals, and removing impurities.

Benefits of technology

This improved the crystallinity and mechanical strength of the cathode material, reduced the probability of electrolyte side reactions, enhanced the cycle life and electrochemical performance of the material, and achieved efficient resource regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120955252A_ABST
    Figure CN120955252A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery materials, in particular to a regeneration method of a waste lithium battery positive electrode material, which comprises the following steps: step 1, disassembling and separating an aluminum foil wrapped positive electrode material; 2, stripping to obtain positive electrode material powder; step 3, obtaining the lithium 2-acrylamide-2-methyl propanesulfonate; step 4, carrying out regeneration treatment to obtain LiF-PAMPS powder; step 5, precursor preparation: mixing the LiF-PAMPS powder and the positive electrode material powder to obtain a composite positive electrode precursor; 6, carrying out gradient heating treatment to obtain a positive electrode activated material; and step 7, performing post-treatment to obtain the positive electrode regenerated material. The positive electrode material of the waste lithium iron phosphate battery is subjected to regeneration treatment and is applied to the lithium battery as the positive electrode material, and detection shows that the positive electrode material not only has excellent rate characteristic and cycle life, but also has high compaction density and high first discharge specific capacity, and the migration ability of lithium ions in the material is relatively strong.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials, and more specifically to a method for regenerating cathode materials from waste lithium batteries. Background Technology

[0002] Lithium-ion batteries, as core components for energy storage, are ubiquitous, from electric vehicles to portable electronic devices. However, with the end of their lifespan, the proper disposal of these used batteries is not only crucial for the efficient use of resources but also poses a significant challenge to environmental protection. Currently, my country has over 580,000 tons of retired power batteries, and the power battery recycling market is projected to exceed 100 billion yuan by 2030. However, the power battery recycling industry is still in its infancy, with a standardized recycling rate of less than 25%. This situation not only wastes resources but also poses potential environmental pollution risks. Lithium-ion batteries contain valuable metals such as nickel, cobalt, and lithium; improper handling can lead to electrolyte leakage, short circuits, and even fires and explosions, seriously threatening the environment and safety. Therefore, establishing efficient recycling methods and improving battery material regeneration technologies have become crucial tasks for the industry's development.

[0003] Lithium iron phosphate (LFP) batteries, with their high safety and low price advantages, not only firmly occupy a dominant position in the energy storage field, but have also regained a significant share of the automotive power battery market as subsidies for new energy vehicles are gradually phased out. Consequently, an increasing number of LFP batteries will be generated as waste batteries in the coming years. Harmless treatment of waste LFP batteries and recycling of electrode materials can not only help alleviate environmental pollution but also extend the lifespan of cathode materials, allowing them to achieve better economic benefits. However, the dismantling and electrode sorting of waste LFP batteries, both domestically and internationally, are mostly done manually, which is not only inefficient but also poses potential hazards to personnel and the environment due to volatile electrolytes and other substances. Furthermore, both wet recycling of valuable metals and LFP remanufacturing processes generate significant amounts of waste liquid and gas, coupled with high energy consumption, resulting in low overall economic benefits for the comprehensive recycling and utilization of LFP batteries. Therefore, to address the problem of the harmless treatment and resource reuse of the ever-growing number of retired LFP batteries, a method for treating LFP cathode materials in a green, low-carbon, and regenerative manner is needed. Summary of the Invention

[0004] To address the problems existing in the prior art, the purpose of this invention is to provide a method for regenerating waste lithium battery cathode materials.

[0005] The objective of this invention is achieved through the following technical solution:

[0006] In a first aspect, the present invention provides a method for regenerating waste lithium battery cathode materials, comprising the following steps:

[0007] Step 1, Disassembly: First, discharge the used lithium iron phosphate batteries, then disassemble them to separate the positive electrode material wrapped in aluminum foil.

[0008] Step 2, peeling: The disassembled aluminum foil-wrapped positive electrode material is added to an organic solvent, ultrasonically treated, and the aluminum foil is peeled off. The positive electrode material is collected, washed and dried, and then pulverized to obtain positive electrode material powder.

[0009] Step 3, Raw material preparation: Add 2-acrylamide-2-methylpropanesulfonic acid (AMPS) and lithium carbonate to deionized water and stir at 60-80℃ for 2-3 hours to obtain lithium 2-acrylamide-2-methylpropanesulfonic acid (Li-AMPS).

[0010] Step 4, preparation of regenerator: Lithium 2-acrylamide-2-methylpropanesulfonate (Li-AMPS) and dodecafluoroheptyl methacrylate (DFHMA) are mixed in anhydrous ethanol, an initiator and a crosslinking agent are added, and the mixture is heated to 65-85℃ under nitrogen protection and stirred for 4-8 hours. After the reaction is completed, the solvent is removed under reduced pressure and dried to obtain LiF-PAMPS powder.

[0011] Step 5, Precursor preparation: Mix LiF-PAMPS powder and anhydrous ethanol, stir thoroughly, then add cathode material powder and mix evenly, then hot press to form a composite cathode precursor.

[0012] Step 6, Temperature Activation: The composite cathode precursor is subjected to gradient temperature treatment and then naturally cooled in the furnace to obtain the cathode activation material.

[0013] Step 7, Post-processing: The positive electrode activation material is ball-milled and magnetically separated to remove ferromagnetic impurities, thus obtaining the positive electrode regenerated material.

[0014] Preferably, in step 1, the discharge treatment method includes one of the following: salt water immersion method, resistance discharge method, and equipment discharge method. More preferably, the discharge involves immersing the battery material in a 0.5-5 mol / L sodium chloride solution for at least 24 hours, followed by drying at 60°C for 12 hours. If the detected voltage is less than 1V, the discharge meets the standard.

[0015] Preferably, in step 1, the waste lithium iron phosphate batteries are of model LFP18650, LFP26650, LFP32650, or LFP104450, and are cylindrical or square aluminum-cased batteries; the positive electrode composition is lithium iron phosphate (LFP) coated with aluminum foil; the capacity range is 1.5-3.5Ah.

[0016] Preferably, in step 2, the organic solvent is N-methylpyrrolidone (NMP) or N,N-dimethylformamide (DMF).

[0017] Preferably, in step 2, the ultrasound is performed using ultrasound with a power of 300-500W at a temperature of 40-50°C for 30-60 minutes.

[0018] Preferably, in step 2, the washing is performed by rinsing three times with ethanol / acetone to remove residual electrolyte, and the drying is performed by drying in a vacuum drying oven at 80°C for 12 hours.

[0019] Preferably, in step 3, the mass ratio of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), lithium carbonate, and deionized water is 2.1:1.5-1.8:10-20.

[0020] Preferably, in step 4, the mass ratio of lithium 2-acrylamide-2-methylpropanesulfonate (Li-AMPS), dodecafluoroheptyl methacrylate (DFHMA), and anhydrous ethanol is 1.47:1.2-1.5:25-35.

[0021] Preferably, in step 4, the initiator is azobisisobutyronitrile (AIBN), and the amount added is 2%-6% of the mass of lithium 2-acrylamide-2-methylpropanesulfonate (Li-AMPS).

[0022] Preferably, in step 4, the crosslinking agent is polyethylene glycol diacrylate with a molecular weight of 1000, and the amount added is 5%-10% of the mass of lithium 2-acrylamide-2-methylpropanesulfonate (Li-AMPS).

[0023] Preferably, in step 5, the mass ratio of LiF-PAMPS powder, cathode material powder, and anhydrous ethanol is 3-5:95-97:30-40.

[0024] Preferably, in step 5, the hot pressing parameters are: hot pressing at 75-85℃ and 5-8MPa for 10-20 minutes.

[0025] Preferably, in step 6, the gradient heating process includes: a first stage of heating to 250-300℃ and holding for 1-2 hours in a mixed atmosphere of argon and hydrogen, wherein the volume ratio of argon to hydrogen is 95:5; a second stage of heating to 550-600℃ and holding for 1-2 hours in an air atmosphere; and a third stage of maintaining the air atmosphere and continuing to heat to 700-750℃ and holding for 2-3 hours.

[0026] Preferably, in step 6, the heating rate of the gradient heating is maintained at 5°C / min to avoid thermal stress cracking.

[0027] Preferably, in step 6, the first stage of low temperature is used to decompose Li-AMPS to release SO2 and reduce high-valence metals, while DFHMA fluorocarbon chains melt and coat the particle surface; the second stage of medium temperature is used to decompose lithium sulfonate into Li2O to penetrate the lattice and replenish lithium, repairing the lattice and stabilizing the layered structure; the third stage of high temperature is used to reconstruct LiFePO4 crystals, while fluorocarbon chains carbonize to form a conductive network.

[0028] Preferably, in step 7, the ball milling speed is 200-300 rpm and the time is 2-4 hours.

[0029] Preferably, in step 7, the magnetic separation intensity is 0.3-0.5T, the purpose of which is to remove impurities from Fe or Ni particles.

[0030] Secondly, the present invention provides a regenerated cathode material, which is prepared by the above-described regeneration method.

[0031] Thirdly, the present invention provides an application of a recycled cathode material in lithium batteries.

[0032] A button cell is assembled using recycled positive electrode material as the positive electrode, lithium metal sheet as the negative electrode, and 1 mol / L LiPF6 / EC:DEC electrolyte; the voltage range is 3.0-4.2V.

[0033] The beneficial effects of this invention are as follows:

[0034] 1. This invention regenerates the cathode material of waste lithium iron phosphate batteries to obtain a regenerated cathode material. When this material is used as a cathode material in lithium batteries, tests show that it not only has excellent rate performance and cycle life, but also high compaction density, high initial discharge specific capacity, and strong lithium ion migration ability within the material.

[0035] 2. This invention involves sequentially splitting, peeling, regenerating, activating, and post-processing the cathode material of spent lithium batteries. The biggest difference between this invention and traditional regeneration methods lies in the introduction of a fluorinated copolymer, LiF-PAMPS, as a lithium source and coating layer during the cathode material regeneration process. LiF-PAMPS is obtained through the cross-linking polymerization of lithium 2-acrylamido-2-methylpropanesulfonate and dodecafluoroheptyl methacrylate. During hot pressing, this fluorinated copolymer adheres tightly to the surface of the cathode particles, forming uniform ion channels. Simultaneously, during the subsequent high-temperature reconstruction of LiFePO4 crystals, the fluorocarbon chains carbonize to form a conductive network.

[0036] 3. The high-temperature reconstruction method of LiFePO4 crystal repair in this invention involves stepwise temperature increase activation, removing residual PVDF and electrolyte in stages, and simultaneously repairing oxygen vacancies, ultimately achieving the generation of a layered structure. Compared to traditional solid-state sintering, this invention avoids lithium volatilization and phase transition caused by single high-temperature treatment, and also increases the crystallinity of the recycled material by more than 15%.

[0037] 4. During the cathode material repair process, the fluorine provided by LiF-PAMPS can form LiF-CoF at high temperatures. x The interface layer not only significantly reduces the probability of side reactions in the electrolyte, but also inhibits oxygen evolution under high voltage. In addition, the copolymer improves the mechanical strength of the material, alleviates particle cracking caused by cyclic stress, and enables the compaction density to reach a high level. Attached Figure Description

[0038] The present invention will be further described with reference to the accompanying drawings, but the embodiments in the drawings do not constitute any limitation on the present invention. For those skilled in the art, other drawings can be obtained based on the following drawings without creative effort.

[0039] Figure 1 This is a SEM image of the positive electrode regenerable material prepared in Example 1 of this invention; Detailed Implementation

[0040] To better understand the above technical solutions, exemplary embodiments of the present invention are described in more detail below. While exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the invention to those skilled in the art.

[0041] The present invention will be further described below with reference to the following embodiments.

[0042] Example 1

[0043] A method for regenerating waste lithium battery cathode materials includes the following steps:

[0044] Step 1: Discharge the waste cylindrical aluminum-cased lithium iron phosphate battery (3.7V) of model LFP18650 by soaking it in a 2mol / L sodium chloride solution for at least 24 hours, then washing it with water and drying it at 60°C for 12 hours. If the voltage is less than 1V, the discharge is considered to be up to standard. Then, disassemble it and separate the positive electrode material wrapped in aluminum foil.

[0045] Step 2: Immerse the disassembled aluminum foil-wrapped positive electrode material in N-methylpyrrolidone (NMP), treat it with ultrasound at 400W and 45°C for 40 minutes, peel off the aluminum foil, collect the positive electrode material, rinse it three times with ethanol to remove residual electrolyte, dry it in a vacuum drying oven at 80°C for 12 hours, and then pulverize it to obtain positive electrode material powder with a particle size of 2-5μm.

[0046] Step 3: Add 2.1g of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) and 1.6g of lithium carbonate to 15g of deionized water and stir at 70°C for 3h to obtain lithium 2-acrylamide-2-methylpropanesulfonic acid (Li-AMPS).

[0047] Step 4: 1.47g of lithium 2-acrylamide-2-methylpropanesulfonate (Li-AMPS) and 1.3g of dodecafluoroheptyl methacrylate (DFHMA) were mixed into 30g of anhydrous ethanol. 4% of the mass of Li-AMPS, azobisisobutyronitrile (AIBN) was added as an initiator, and 7% of the mass of Li-AMPS, polyethylene glycol diacrylate with a molecular weight of 1000 was added as a crosslinking agent. Under nitrogen protection, the temperature was raised to 75℃ and stirred for 6h. After the reaction was completed, the solvent was removed under reduced pressure and dried to obtain LiF-PAMPS powder.

[0048] Step 5: Mix 4g of LiF-PAMPS powder and 35g of anhydrous ethanol, stir thoroughly, then add 96g of cathode material powder and mix evenly. Then hot press at 80℃ and 6MPa for 15min to form a composite cathode precursor.

[0049] Step 6: The composite cathode precursor is subjected to a stepped heating process, with the heating rate maintained at 5℃ / min to avoid thermal stress cracking: first, it is heated to 300℃ and held for 1 hour in a mixed atmosphere of argon and hydrogen (volume ratio 95:5), then heated to 600℃ and held for 2 hours in an air atmosphere, and finally heated to 750℃ and held for 3 hours while maintaining the air atmosphere; after natural cooling in the furnace, the cathode activation material is obtained.

[0050] Step 7: The positive electrode activation material is ball-milled at a speed of 250 rpm for 3 hours until the median particle size (D50) is 8 μm. Magnetic separation (intensity 0.4T) is then used to remove magnetic impurities from the Fe or Ni particles to obtain the positive electrode regenerated material.

[0051] Example 2

[0052] A method for regenerating waste lithium battery cathode materials includes the following steps:

[0053] Step 1: Discharge the used cylindrical lithium iron phosphate batteries of model LFP26650 by soaking them in a 1 mol / L sodium chloride solution for at least 24 hours, then washing them with water and drying them at 60°C for 12 hours. If the voltage is less than 1V, the discharge is considered to be up to standard. Then, disassemble the batteries and separate the positive electrode material wrapped in aluminum foil.

[0054] Step 2: Immerse the disassembled aluminum foil-wrapped positive electrode material in N-methylpyrrolidone (NMP), treat it with ultrasonic waves at 40°C and 300W for 60 minutes, peel off the aluminum foil, collect the positive electrode material, rinse it three times with acetone to remove residual electrolyte, dry it in a vacuum drying oven at 80°C for 12 hours, and then pulverize it to obtain positive electrode material powder with a particle size of 2-5μm.

[0055] Step 3: Add 2.1g of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) and 1.5g of lithium carbonate to 10g of deionized water and stir at 60℃ for 3h to obtain lithium 2-acrylamide-2-methylpropanesulfonic acid (Li-AMPS).

[0056] Step 4: 1.47g of lithium 2-acrylamide-2-methylpropanesulfonate (Li-AMPS) and 1.2g of dodecafluoroheptyl methacrylate (DFHMA) were mixed into 25g of anhydrous ethanol. 2% of the mass of Li-AMPS, azobisisobutyronitrile (AIBN) was added as an initiator, and 5% of the mass of Li-AMPS, polyethylene glycol diacrylate with a molecular weight of 1000 was added as a crosslinking agent. Under nitrogen protection, the temperature was raised to 65℃ and stirred for 4h. After the reaction was completed, the solvent was removed under reduced pressure and dried to obtain LiF-PAMPS powder.

[0057] Step 5: Mix 3g of LiF-PAMPS powder and 30g of anhydrous ethanol, stir thoroughly, then add 97g of cathode material powder and mix evenly. Then hot press at 75℃ and 5MPa for 20min to form a composite cathode precursor.

[0058] Step 6: The composite cathode precursor is subjected to a stepped heating process, with the heating rate maintained at 5℃ / min to avoid thermal stress cracking: first, it is heated to 250℃ and held for 1 hour in a mixed atmosphere of argon and hydrogen (volume ratio 95:5), then heated to 550℃ and held for 2 hours in an air atmosphere, and finally, it is heated to 700℃ and held for 3 hours while maintaining the air atmosphere; after natural cooling in the furnace, the cathode activation material is obtained.

[0059] Step 7: The positive electrode activation material is ball-milled at a speed of 200 rpm for 4 hours until the median particle size (D50) is 8 μm. Magnetic separation (intensity 0.3T) is then used to remove magnetic impurities from the Fe or Ni particles to obtain the positive electrode regenerated material.

[0060] Example 3

[0061] A method for regenerating waste lithium battery cathode materials includes the following steps:

[0062] Step 1: Discharge the used square aluminum-cased lithium iron phosphate battery (model LFP104450) by soaking it in a 3 mol / L sodium chloride solution for at least 24 hours, then washing it with water and drying it at 60°C for 12 hours. If the voltage is less than 1V, the discharge is considered successful. Then, disassemble the battery and separate the positive electrode material wrapped in aluminum foil.

[0063] Step 2: Immerse the disassembled aluminum foil-wrapped positive electrode material in N,N-dimethylformamide (DMF), treat it with 500W ultrasonic power at 50℃ for 30 minutes, peel off the aluminum foil, collect the positive electrode material, rinse it with ethanol 3 times to remove residual electrolyte, dry it in a vacuum drying oven at 80℃ for 12 hours, and then pulverize it to obtain positive electrode material powder with a particle size of 2-5μm.

[0064] Step 3: Add 2.1g of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) and 1.8g of lithium carbonate to 20g of deionized water and stir at 80℃ for 2h to obtain lithium 2-acrylamide-2-methylpropanesulfonic acid (Li-AMPS).

[0065] Step 4: 1.47g of lithium 2-acrylamide-2-methylpropanesulfonate (Li-AMPS) and 1.5g of dodecafluoroheptyl methacrylate (DFHMA) were mixed into 35g of anhydrous ethanol. Azobisisobutyronitrile (AIBN) of 6% by weight of Li-AMPS was added as an initiator, and polyethylene glycol diacrylate of 1000 molecular weight of Li-AMPS was added as a crosslinking agent. Under nitrogen protection, the temperature was raised to 85℃ and stirred for 4h. After the reaction was completed, the solvent was removed under reduced pressure and dried to obtain LiF-PAMPS powder.

[0066] Step 5: Mix 5g of LiF-PAMPS powder and 40g of anhydrous ethanol, stir thoroughly, then add 95g of cathode material powder and mix evenly. Then hot press at 85℃ and 8MPa for 10min to form a composite cathode precursor.

[0067] Step 6: The composite cathode precursor is subjected to a stepped heating process, with the heating rate maintained at 5℃ / min to avoid thermal stress cracking: first, it is heated to 300℃ and held for 2 hours in a mixed atmosphere of argon and hydrogen (volume ratio 95:5), then heated to 600℃ and held for 2 hours in an air atmosphere, and finally heated to 750℃ and held for 2 hours while maintaining the air atmosphere; after natural cooling in the furnace, the cathode activation material is obtained.

[0068] Step 7: The positive electrode activation material is ball-milled at a speed of 300 rpm for 2 hours until the median particle size (D50) is 8 μm. Magnetic separation (intensity 0.5T) is then used to remove magnetic impurities from the Fe or Ni particles, thus obtaining the positive electrode regenerated material.

[0069] Comparative Example 1

[0070] A method for regenerating waste lithium battery cathode materials, differing from Example 1 only in that the LiF-PAMPS powder used in step 5 is replaced with lithium acetate (conventional method).

[0071] Comparative Example 2

[0072] A method for regenerating waste lithium battery cathode materials, differing from Example 1 only in that the LiF-PAMPS powder used in step 5 is replaced with Li-AMPS (fluorine-free).

[0073] Comparative Example 3

[0074] A method for regenerating waste lithium battery cathode material, differing from Example 1 only in that the LiF-PAMPS powder used in step 5 is replaced with DFHMA (lithium-free).

[0075] To more clearly illustrate the content of the present invention, the cathode materials obtained by regeneration in Example 1 and Comparative Examples 1-3 were respectively applied to batteries, and their electrochemical performance was tested.

[0076] The test conditions were as follows: half-cell (lithium sheet as negative electrode, regenerated positive electrode material as positive electrode), voltage window 3.0-4.2V, electrolyte 1mol / L LiPF6 / EC:DEC (1:1), room temperature 25℃.

[0077] The test results are shown in Table 1-3 below:

[0078] Table 1 Battery performance at different rate

[0079]

[0080] Table 2 Battery performance at 0.5C rate

[0081]

[0082] Table 3 Performance of Battery Materials

[0083]

[0084]

[0085] As can be seen from Tables 1-3, the cathode material obtained by the method of Example 1 exhibits superior rate performance and cycle life. Furthermore, the electrode material has high compaction density, high initial discharge specific capacity, and strong lithium-ion migration capability within the material. In contrast, the initial discharge specific capacity of the conventional Comparative Example 1 decreased by 17%-27% compared to Example 1 at different rates, and its capacity retention rate after 200 cycles at 0.5C was also approximately 20% lower than Example 1. This may be because lithium acetate almost completely decomposes at 500°C, resulting in insufficient lithium source supply, inadequate lithium replenishment, and increased lattice defects. The charge transfer impedance of Comparative Example 1 increased by more than 130%, and the lithium-ion diffusion coefficient decreased by about 50%, possibly due to the presence of acetate ions (CH3COO) in the lithium acetate. - This leads to electrolyte oxidation. In addition, in Comparative Example 2, the lack of fluorinated groups in DFHMA prevents the formation of a LiF interface layer, resulting in a reduced lithium-ion diffusion rate and thus slightly poorer electrochemical performance. In Comparative Example 3, DFHMA does not contain lithium and cannot compensate for lithium volatilization during the sintering process, resulting in lower discharge specific capacity and cycle life.

[0086] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. The illustrative expressions of the above terms in this specification should not be construed as necessarily referring to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.

[0087] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A method for regenerating waste lithium battery cathode material, characterized in that, Includes the following steps: Step 1, Disassembly: First, discharge the used lithium iron phosphate batteries, then disassemble them to separate the positive electrode material wrapped in aluminum foil. Step 2, peeling: The disassembled aluminum foil-wrapped positive electrode material is added to an organic solvent, ultrasonically treated, and the aluminum foil is peeled off. The positive electrode material is collected, washed and dried, and then pulverized to obtain positive electrode material powder. Step 3, Raw material preparation: 2-Acrylamido-2-methylpropanesulfonic acid and lithium carbonate are added to deionized water and stirred at 60-80℃ for 2-3 hours to obtain lithium 2-acrylamido-2-methylpropanesulfonic acid; Step 4, preparation of regenerator: Lithium 2-acrylamide-2-methylpropanesulfonate and dodecafluoroheptyl methacrylate are mixed in anhydrous ethanol, an initiator is added, a crosslinking agent is added, and under nitrogen protection, the temperature is raised to 65-85℃ and stirred for 4-8 hours. After the reaction is completed, the solvent is removed under reduced pressure and dried to obtain LiF-PAMPS powder. Step 5, Precursor preparation: Mix LiF-PAMPS powder and anhydrous ethanol, stir thoroughly, then add cathode material powder and mix evenly, then hot press to form a composite cathode precursor. Step 6, Temperature Activation: The composite cathode precursor is subjected to gradient temperature treatment and then naturally cooled in the furnace to obtain the cathode activation material. Step 7, Post-processing: The positive electrode activation material is ball-milled and magnetically separated to remove ferromagnetic impurities, thus obtaining the positive electrode regenerated material.

2. The method for regenerating waste lithium battery cathode material according to claim 1, characterized in that, In step 1, the discharge treatment method includes one of the following: salt water immersion method, resistance discharge method, and equipment discharge method.

3. The method for regenerating waste lithium battery cathode material according to claim 1, characterized in that, In step 2, the organic solvent is N-methylpyrrolidone or N,N-dimethylformamide; the ultrasonic treatment is performed at 40-500°C using ultrasonic waves with a power of 300-500W for 30-60 minutes.

4. The method for regenerating waste lithium battery cathode material according to claim 1, characterized in that, In step 3, the mass ratio of 2-acrylamide-2-methylpropanesulfonic acid, lithium carbonate, and deionized water is 2.1:1.5-1.8:10-20.

5. The method for regenerating waste lithium battery cathode material according to claim 1, characterized in that, In step 4, the mass ratio of lithium 2-acrylamide-2-methylpropanesulfonate, dodecafluoroheptyl methacrylate, and anhydrous ethanol is 1.47:1.2-1.5:25-35.

6. The method for regenerating waste lithium battery cathode material according to claim 1, characterized in that, In step 4, the initiator is azobisisobutyronitrile, and the amount added is 2%-6% of the mass of lithium 2-acrylamide-2-methylpropanesulfonate; the crosslinking agent is polyethylene glycol diacrylate with a molecular weight of 1000, and the amount added is 5%-10% of the mass of lithium 2-acrylamide-2-methylpropanesulfonate.

7. The method for regenerating waste lithium battery cathode material according to claim 1, characterized in that, In step 5, the mass ratio of LiF-PAMPS powder, cathode material powder, and anhydrous ethanol is 3-5:95-97:30-40.

8. A method for regenerating waste lithium battery cathode material according to claim 1, characterized in that, In step 5, the hot pressing parameters are: hot pressing at 75-85℃ and 5-8MPa for 10-20 minutes.

9. A method for regenerating waste lithium battery cathode material according to claim 1, characterized in that, In step 6, the gradient heating process includes: the first stage is to heat to 250-300℃ in a mixed atmosphere of argon and hydrogen and hold for 1-2 hours, wherein the volume ratio of argon to hydrogen is 95:5; the second stage is to heat to 550-600℃ in an air atmosphere and hold for 1-2 hours; the third stage is to maintain the air atmosphere and continue to heat to 700-750℃ and hold for 2-3 hours.

10. A method for regenerating waste lithium battery cathode material according to claim 1, characterized in that, In step 7, the ball milling speed is 200-300 rpm and the time is 2-4 h; the magnetic separation intensity is 0.3-0.5 T, the purpose of which is to remove impurities from Fe or Ni particles.